On becoming literate in English: a literate life history study of selected Grade 12 learners in a Namibian secondary school - Kangootui, Angela Lydia (Rhodes University, Faculty of Education, Department of Education, 2018)
This study sought to investigate English literate journeys of selected Grade 12 learners who come from educationally disempowering home backgrounds, and who 'meet' informal and/or formal exposure to English language mainly within the confines of school hours. Located within the qualitative, interpretive life history study design, the study used questionnaire and learners' autobiographies to generate data. These data were then subjected to explore the literate journey of these learners in English as a second language through a comprehensive descriptive analysis. The study was conducted in an urban high school in Omaheke region, Namibia, and the research site and study participants were selected purposively. Theoretically, the study drew from Krashen's (1981) Second Language Acquisition Theory, which offered this study the five hypotheses that were used as categories to generate, analyse, interpret and discuss data. Research findings reveal that, for various reasons discussed in the study, there is minimal parental involvement in the English literacy journey of their children at home. These include parents not reading regularly to their children, not encouraging visits to the library and the shortage of literacy materials such as newspapers and magazines. The educational level of parents is also a major contributing factor in the literacy journey of their children. The contribution of the community towards the literacy journey in English as a second language of these learners was minimal since the vernacular languages or Afrikaans were used to communicate. At the school level it was found that the attitude of some teachers was a hindrance, as was the way they taught. The use of the mother tongue during teaching also had an effect on the literacy development of the learners. Although the different methods used by various teachers at school level contributed in a way towards literacy development of the learners at school, the huge number of learners in the classrooms was a force to be reckoned with. It is hoped that the study's findings will assist the Ministry of Basic Education Arts and Culture (MBEAC) in Namibia in informing the type of syllabus content and pedagogical practices to be utilised in teaching English as a Second Language.
Keywords: English language -- Study and teaching (Secondary) -- Namibia -- Omaheke; Second language acquisition -- Omaheke; Language and languages -- Study and teaching -- Namibia -- Omaheke; Namibia. Ministry of Basic Education, Sport, and Culture